Essays on population economics: the national transfer accounts in Brazil - Correa, Charles Henrique (2025)
In Brazil, the increase in life expectancy and the decline in fertility over recent decades have transformed the size and age structure of the population. These demographic changes impact economic activity, especially regarding consumption, labor income, and intergenerational trans fers. Although the country regularly publishes the System of National Accounts, it has not yet officially released the National Transfer Accounts (NTA), a systematic and comprehensive satellite-account that enables the analysis of the economic impacts of demographic changes. This doctoral dissertation focuses on two approaches to measure and analyze the NTA in Brazil. In the first approach, a traditional estimate of the NTA shows how changes in population size and age structure contributed to explaining changes in consumption and labor income between 2003 and 2018. Additionally, the estimates reveal how individuals whose labor income exceeds their consumption transfer resources to those with little or no labor income. In the second approach, an extended version of the NTA disaggregates the estimates by educational attainment of household heads in 2018, highlighting social disparities that could be obscured by the average estimates in the first approach. In both cases, the compilation followed the standard methodology of the United Nations (2013), using a comprehensive set of data from national accounts, household surveys, administrative records, and population estimates. The results revealed both intergenera tional and intragenerational disparities throughout the economic life cycle in Brazil. Children and the older population (deficit generations) were especially dependent on resource transfers from the working-age population (surplus generations) due to their limited or absent labor income. During the demographic bonus between 2003 and 2018, population growth and aging contributed to a 27.5% increase in labor income and a 28.6% increase in tax revenues, which facilitated these intergenerational resource transfers. The decline in the proportion of children, as a result of population aging during the period, reduced the pressure on education expenditures by 20.0% in the public sector and 14.3% in the private sector. Overall, the country capitalized on the educa tional bonus, with a real increase in per capita investment in education over the period. However, population aging led to a 43.1% increase in pension expenditures (RGPS) and a 17.2% increase in public health spending. Moreover, the results suggested that workers in households with lower educational attainment had significantly lower labor income during the productive ages, limiting their capacity to transfer resources to children and the older population in these social groups. In this case, the government played a redistributive role in the provision of goods and services, such as public healthcare and education, helping to reduce consumption disparities across populations with different education levels. In summary, this study contributed to showing how demographic changes—particularly those related to population growth and aging—have driven both economic opportunities and challenges. The country partially experienced the benefits of the demographic and educational bonus but has faced growing pressures on public expenditures, such as pensions and healthcare, in a context of population aging and social inequality.